Old Times, Better Times? German Miners' Knappschaften, Pay-as-you-go Pensions, and Implicit Rates of Return, 1854–1913 - Tobias Alexander Jopp (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This paper contributes to the literature on the weakness of modern pay-as-yougo social security systems in financing pensions by taking a business and economic historical perspective on the issue. It focuses on Prussian Knappschaften (plural of Knappschaft), which provided miners with compulsory invalidity and implicit old-age insurance, and studies the period from 1854 to 1913. Knappschaften used the pay-asyou-go mechanism, and, in the long-term, came under financial pressure by the rising number of pensioners. The question to be answered is whether Knappschaften were able to offer cohorts of miners entering the system at different times the same implicit rates of return. Did Knappschaften provide an intergenerationally sustainable policy, or did adjustments of contributions and other parameters decrease the dividend for insured miners over time? – – Dieser Aufsatz leistet aus wirtschaftshistorischer Perspektive einen Beitrag zum Verständnis der Schwächen moderner umlagefinanzierter Sozialversicherungssysteme. Im Mittelpunkt stehen dabei die Knappschaftsvereine Preußens, die Träger der bergbau-spezifischen Sozialversicherung, welche insbesondere Invaliditäts- bzw. implizite Altersrenten gwährten, sowie der Zeitraum 1854-1913. Die Knappschaftsvereine arbeiteten auf Basis des Umlageverfahrens und sahen sich langfristig der Herausforderung steigender Rentenempfänger-Beitragszahler-Quotienten ausgesetzt. Dies wirft rückschauend die Frage auf, ob es für die Knappschaftsvereine möglich war, verschiedenen Eintrittskohorten von Versicherten dieselbe implizite Rendite zu gewähren. War also deren Geschäftspolitik dennoch intergenerational ausgeglichen oder führten unausweichliche Anpassungen des Beitragssatzes und anderer Größen zu im Zeitablauf sinkenden Renditen?
Keywords: N33; N83; H53; H55; 330; insurance; implicit rates of return; Knappschaft; mining; pay-as-you-go; pensions; Prussia; welfare state